Pengaruh Perceived Person-Organization Fit Terhadap Organizational Citizenship Behavior Dengan Mediasi Organizational Commitment Pada Karyawan PT “X” - Rini Nurahaju; Lailatus Saniyah; Nurul Sih Widanti (CV. Ulil Albab Corp, 2026)
This study aims to determine the direct and indirect effect of Perceived Person-Organization Fit on Organizational Citizenship Behavior through Organizational Commitment to employees of PT “X”. This study uses a quantitative approach technique with survey methods and analytical techniques in the form of path analysis. The total of subjects in this study were 131 respondents who were employees of PT “X”. The sampling technique uses non-probability sampling with a sampling technique in the form of a saturated sample. The results of the study show a direct effect of Perceived Person-Organization Fit on Organizational Citizenship Behavioras big 28.5%. The results of the influence of Perceived Person-Organization Fit on Organizational Commitment as big 24.5%. The results of influence Organizational Commitment to Organizational Citizenship Behavior of 36.3%. The results of indirect influence between Perceived Person-Organization Fit to Organizational Citizenship Behavior through Organizational Commitment by 8.9% and the mediating effect that occurs in this study is partial mediation.